A revision of Lomachaeta Mickel, with a new species of Smicromutilla Mickel (Hymenoptera: Mutillidae) - Pitts, James P.; Manley, Donald G. (Zootaxa, 2004)
The following species of Lomachaeta are described as new: L. argenta (Utah, USA), L. chionothrix (Guatemala), L. cirrhomeris (Southwestern USA), L. crocopinna (Southwestern USA), L. hyphantria (Bolivia) and L. ptilohyalus (Mexico). Dasymutilla mickeli Manley and Deyrup, Lomachaeta coloradensis Mickel, Lomachaeta formosula Mickel, L. minutula Mickel, L. punctinota Mickel, and L. variegata Mickel are junior synonyms of L. hicksi Mickel; Lomachaeta hicksi has page priority. New distributional data are presented L. hicksi Mickel. A revised key, diagnoses for the species, and host data are provided for the species of Lomachaeta. The genus Smicromutilla is also reviewed and a new species of Smicromutilla from California is described as S. beadugrimi.